A new species of Tradescantia L. sect. Austrotradescantia D.R.Hunt (Commelinaceae) from Southern Brazil - Pellegrini, Marco Octávio De Oliveira (Phytotaxa, 2016)
A new species of Tradescantia sect. Austrotradescantia endemic to rocky cliffs in Southern Brazil, is here described as Tradescantia seubertiana. This new species is characterized as being completely glabrous, with a leaf base obtuse to cordate to slightly amplexicaulous, ellipsoid flower buds, by its light-pink to pink petals, and for growing in wet rocky cliffs. The new species is morphologically most similar to T. crassula due to its erect habit, conduplicate to canaliculate, succulent leaves, with inconspicuous secondary veins, non-saccate cincinni bracts, pistil longer than the stamens and hilum longer than ½ the length of the seed. I present a description, an illustration, a distribution map, habitat description, and a conservation assessment for the new species. I also present a comparison and identification key for the species related to T. seubertiana.